2004
DOI: 10.1002/meet.14504101102
|View full text |Cite
|
Sign up to set email alerts
|

Blogs for information dissemination and knowledge management

Abstract: Blogging has begun to enter the mainstream, showing valuable knowledge management tools, especially for up in knowledge management initiatives and in corporate teams." In this session, active bloggers will talk about the and academic libraries. Lou Rosenfeld. in his blog, says use of blogs and k-logs (knowledge weblogs) for that k-logs "promise to be inexpensive, lightweight, and information dissemination within organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, the web log is discussed in relation to other technologies such as the semantic web (Karger & Quan, 2005), wireless (Leu, Chi, & Shih, 2005), and networked personal digital assistants (Todoroki, Konishi, & Inoue, 2006). The relationship between this technology and information dissemination is relevant as well (Bar-llan, 2005;Liberman, Baumgart, Eastman, & Pikas, 2005). Technorati.com (2006), the web log search engine reported that between March 2003 and April 2006 the blogosphere doubled in size every six months.…”
Section: Blogging Trendsmentioning
confidence: 99%
“…In addition, the web log is discussed in relation to other technologies such as the semantic web (Karger & Quan, 2005), wireless (Leu, Chi, & Shih, 2005), and networked personal digital assistants (Todoroki, Konishi, & Inoue, 2006). The relationship between this technology and information dissemination is relevant as well (Bar-llan, 2005;Liberman, Baumgart, Eastman, & Pikas, 2005). Technorati.com (2006), the web log search engine reported that between March 2003 and April 2006 the blogosphere doubled in size every six months.…”
Section: Blogging Trendsmentioning
confidence: 99%
“…Blogs are discussed in relation to other technologies such as the semantic web (Karger & Quan, 2005), wireless (Leu, Chi, & Shih, 2005), and networked personal digital assistants (Todoroki, Konishi, & Inoue, 2006). The relationship between this technology and information dissemination is relevant as well (Bar-llan, 2005;Liberman, Baumgart, Eastman, & Pikas, 2005).…”
Section: Research Gapmentioning
confidence: 99%